Decreased plasma kallikrein activity is associated with reduced kidney function in individuals with type 1 diabetes - Härmä Mari-Anne; Dahlström Emma H; Sandholm Niina; Forsblom Carol; Groop Per-Henrik; Lehto Markku; on behalf of FinnDiane Study Group (SPRINGER, 2025)
Aims/hypothesis
Plasma kallikrein is the central mediator of the plasma kallikrein-kinin system, which is involved both in vascular control and thrombin formation cascades. The plasma kallikrein-kinin system has also been considered protective in pathological conditions, but the impact of plasma kallikreins on diabetic nephropathy remains unknown. The objective of this cross-sectional study was to explore the association of plasma kallikrein with diabetic nephropathy.
Methods
We measured plasma kallikrein activity in 295 individuals with type 1 diabetes at various stages of diabetic nephropathy, and we tested the genetic association between the plasma kallikrein-kinin system and kidney function in 4400 individuals with type 1 diabetes.
Results
Plasma kallikrein activity was associated with diabetes duration (p < 0.001) and eGFR (p < 0.001), and plasma kallikrein activity was lower with more advanced diabetic nephropathy, being lowest in individuals on dialysis. The minor alleles of the KNG1 rs5030062 and rs710446 variants, which have previously been associated with increased plasma pre-kallikrein and/or factor XI (FXI) protein levels, were associated with higher eGFR (rs5030062 beta = 0.03, p = 0.01; rs710446 beta = 0.03, p = 0.005) in the FinnDiane cohort of 4400 individuals with type 1 diabetes.
Conclusions/interpretation
Plasma kallikrein activity and genetic variants known to increase the plasma kallikrein level are associated with higher eGFR in individuals with type 1 diabetes, suggesting that plasma kallikrein might have a protective effect in diabetic nephropathy.